2019
DOI: 10.1155/2019/7403104
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Mechanical Thrombectomy for Stroke: A Meta-Analysis

Abstract: Mechanical thrombectomy (MT) has become the standard treatment for large vessel occlusion (LVO) in acute ischemic stroke (AIS). Few studies have investigated long-term outcomes for AIS treated with MT. Therefore, a pooled meta-analysis using data from randomized clinical trials (RCT) was performed to assess for long-term clinical outcomes. A systematic literature search was conducted on 27 September 2017, by searching the English literature in the Cochrane Library, MEDLINE, and Embase for RCTs investigating lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…Aspiration devices achieve consistently high recanalization rates (68–100%), but clinical outcomes with aspiration are variable with studies showing very poor recovery rates 18 . ASTER trial showed no difference and no inferiority was shown in COMPASS trial and post‐hoc analysis of Mr CLEAN did not demonstrate any trends in outcome when comparing the two different approaches 19‐24 , 26 . While some evidence is emerging to suggest that either approach may be more efficient as a first line in different scenarios, for example, Ye et al reported 89% successful revascularisationusing ADAPT in basilar artery occlusion versus 83% using stent retreiver as first line, neurointerventionists have shifted strategy to combined approaches of which several are already reported in the literature 22,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration devices achieve consistently high recanalization rates (68–100%), but clinical outcomes with aspiration are variable with studies showing very poor recovery rates 18 . ASTER trial showed no difference and no inferiority was shown in COMPASS trial and post‐hoc analysis of Mr CLEAN did not demonstrate any trends in outcome when comparing the two different approaches 19‐24 , 26 . While some evidence is emerging to suggest that either approach may be more efficient as a first line in different scenarios, for example, Ye et al reported 89% successful revascularisationusing ADAPT in basilar artery occlusion versus 83% using stent retreiver as first line, neurointerventionists have shifted strategy to combined approaches of which several are already reported in the literature 22,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Stent-retriever thrombectomy shows that patients achieve high rates of good clinical outcome after 90-days 76 and there is evidence that this benefit over standard medical therapy persists for up to one year. 77 This may suggest, as do preclinical models, that the artery remodels and the injury is resolved. However, vascular imaging is not routinely acquired during long-term follow-up and vascular remodeling process in patients following stent-retriever thrombectomy remains largely unknown.…”
Section: Distal Emboli and Vascular Traumamentioning
confidence: 99%
“…Those that have been reported are symptomatic intracranial hemorrhage within 36 hours, subarachnoid hemorrhage (SAH), air emboli, vessel dissection, major groin complications, and emboli to new vascular territories. [1][2][3] We present a case of a patient who received mechanical thrombectomy, and on post procedure imaging was found to have artifact suggestive of a retained stent retriever or catheter remnant.…”
Section: Introductionmentioning
confidence: 98%
“…Complications from this procedure are uncommon. Those that have been reported are symptomatic intracranial hemorrhage within 36 hours, subarachnoid hemorrhage (SAH), air emboli, vessel dissection, major groin complications, and emboli to new vascular territories …”
Section: Introductionmentioning
confidence: 99%